2006
DOI: 10.1080/00016340600780508
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity related to maternal group B streptococcal infections

Abstract: Group B streptococcus is known to be a leading cause of neonatal infection, but less appreciated is the fact that it causes maternal infection also. Maternal group B streptococcal infections during pregnancy and delivery threaten not only the mother, but the child as well. Postpartum infection, such as mastitis, bacteremia, sepsis, meningitis, endometritis, and wound infections are hazards to the mother. We describe the various maternal group B streptococcal infections, their characteristics, associated neonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 106 publications
2
64
0
5
Order By: Relevance
“…This is consistent with findings in other studies (Aungst et al, 2004, Le et al, 2004. However, several studies have reported high rates of GBS UTI in non-pregnant adults (Edwards&Baker, 2005, Falagas et al, 2006, Muller et al, 2006, Toumi et al, 2006. In one study, GBS was cultured from 39% of all cases of symptomatic UTI among nursing home residents >70 years of age (Trivalle et al, 1998).…”
Section: Prevalence Of Gbs In the Urinary Tractsupporting
confidence: 82%
See 3 more Smart Citations
“…This is consistent with findings in other studies (Aungst et al, 2004, Le et al, 2004. However, several studies have reported high rates of GBS UTI in non-pregnant adults (Edwards&Baker, 2005, Falagas et al, 2006, Muller et al, 2006, Toumi et al, 2006. In one study, GBS was cultured from 39% of all cases of symptomatic UTI among nursing home residents >70 years of age (Trivalle et al, 1998).…”
Section: Prevalence Of Gbs In the Urinary Tractsupporting
confidence: 82%
“…Pyuria concurrently with bacteriuria constitutes diagnostic criteria in some settings (Shaikh et al, 2007), although what constitutes clinically significant bacteriuria is not strictly defined; colony counts >10 3 cfu/ml of a uropathogen is however, now widely accepted diagnostic criteria for cystitis (Nicolle, 2008, Rubin et al, 1992. Clinically, UTI due to GBS may be indistinguishable from UTI caused by other uropathogens (Muller et al, 2006). A recent study of multiple uropathogens highlighted unique frequencies of host characteristics in UTI groups defined by the causal organism (Tabibian et al, 2008).…”
Section: Diagnosis Of Gbs Utimentioning
confidence: 99%
See 2 more Smart Citations
“…Many of these episodes represent ABU (2, 18); however, GBS ABU is considered to be a surrogate for heavy maternal colonization (29,42) and is currently recommended for intrapartum antibiotic chemoprophylaxis (23,34). In addition, up to 7% of pregnancies may be complicated by GBS UTI, and GBS reportedly accounts for approximately 10% of all cases of pyelonephritis during pregnancy (25,28). …”
mentioning
confidence: 99%